Urinary screening for detection of renal abnormalities in asymptomatic pre-school children referred to Ardabil city health centers from 2016 to 2017 - Mohammadi-Kebar, Susan; Zarea-noghabi, Javed; Hoseininia, Saeid; Mahmoudi, Davoud (International Surgery Journal, 2020)
Background: Urinary screening for detection of proteinuria, hematuria, and pyuria for early diagnosis curable or preventable renal disease in three decade has been considered. The aim of this study was urinary screening for Detection of renal abnormalities in asymptomatic pre-school children referred to health center in Ardabil city from 2016 to 2017. Methods: This was a cross-sectional descriptive study that has been done on urine specimens of 350 children who referred to Ardabil city health center to injection DTP vaccine from April 2016 to Sep 2017. In these infants, proteinuria, hematuria, pyuria and urinary casts were examined and abnormal finding were referred to future investigation to nephrologist. Information was collected and analyzed by statistical methods in SPSS version 21. Results: A total of 350 children were enrolled in the study. There were 196 (56%) boys and 154 (44%) girls. The prevalence of urinary abnormalities in all children was 8.3%. Of all urinary abnormalities, proteinuria and hematuria were detected in 12 children (3.44 %). Of all infants, 9 children (2.57%) had pyuria. Also, 6 children (1.8%) had urinary casts that of them two cases had acid ureic cast and four cases had calcium oxalate cast. Conclusions: This study showed that the prevalence of urinary abnormalities in Ardabil city children was similar to other studies in other country or cities. The reasons of this may be different in race and ethnic. We suggest that routine urinalysis should be part of screening of children at the school entry in Ardabil.